Trees Configuration Effect on Wind as Thermal ENvironment Elemen in Anun-Alun Merdeka Kota Malang - Ratna Arianda Juwita; Jono Wardoyo (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
Thermal environment in green open spaces in tropics is influenced by several factors. Trees configuration are one of the factors. Trees play a role in conditioning thermal comfort through filtrating, directing, blocking, deflecting and causing turbulence to occur in local microclimate. This study examines the speed and flow of wind caused by tree configuration in Alun-Alun Merdeka Kota Malang as one of the microclimate controllers and recharge areas, using field measurements and descriptive evaluative methods and wind tunnel simulations using Autodesk Flow Design software. The results indicate that in the morning the speed and flow of wind at all measuring points have the interval between0.6-1.4 m/s and are considered into comfortable wind speed category, but in the afternoon wind speed interval is 0.73-2,07 m/s, there were 11 measuring points with rather uncomfortable wind speeds and 4 measuring points with comfortable wind speeds. The best tree configuration pattern in Merdeka Square in Malang is a cluster and linear configuration pattern with a medium tree arrangement that has rounded shaped crown that does not hinder windflow from the south and south southeast, but also can create turbulence in windshield area. Addition and rearrangement of configuration patterns need to be done to recreate comfortable wind speeds based on the activities that occur.